2017
DOI: 10.1002/chem.201604889
|View full text |Cite
|
Sign up to set email alerts
|

How Does CeIII Nitrate Dissolve in a Protic Ionic Liquid? A Combined Molecular Dynamics and EXAFS Study

Abstract: A diluted solution of Ce(NO ) in the protic ionic liquid (IL) ethylammonium nitrate (EAN) was investigated using molecular dynamics (MD) simulations and extended X-ray absorption fine structure (EXAFS) spectroscopy. For the first time polarizable effects were included in the MD force field to describe a heavy metal ion in a protic IL, but, unlike water, they were found to be unessential. The Ce ion first solvation shell is formed by nitrate ions arranged in an icosahedral structure, and an equilibrium between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 68 publications
2
18
0
Order By: Relevance
“…In a previous investigation on the solvation properties of Ce(NO 3 ) 3 in EAN, it was shown that such feature in the FT is due to multiple scattering effects of the nitrate ligands. 27 Therefore, the increase of this peak intensity shows that at higher EAN concentrations, more and more nitrate anions enter the La 3+ solvation complex. It is important to stress that very similar EXAFS spectra and FTs have been obtained for mixtures with similar compositions, such as those with χ EAN = 0.1 and χ EAN = 0.2, or with χ EAN = 0.8 and χ EAN = 1.0, suggesting that the structure of the La 3+ ion first solvation shell is very similar in these composition ranges.…”
Section: Resultsmentioning
confidence: 96%
“…In a previous investigation on the solvation properties of Ce(NO 3 ) 3 in EAN, it was shown that such feature in the FT is due to multiple scattering effects of the nitrate ligands. 27 Therefore, the increase of this peak intensity shows that at higher EAN concentrations, more and more nitrate anions enter the La 3+ solvation complex. It is important to stress that very similar EXAFS spectra and FTs have been obtained for mixtures with similar compositions, such as those with χ EAN = 0.1 and χ EAN = 0.2, or with χ EAN = 0.8 and χ EAN = 1.0, suggesting that the structure of the La 3+ ion first solvation shell is very similar in these composition ranges.…”
Section: Resultsmentioning
confidence: 96%
“…Its viscosity is known as a function of temperature [36]; it is 37.4 mPa.s at 22 • C. EAN molecules form a network of hydrogen bonds, similar to that of water [37], and the small ethyl chain induces a sponge-like structure in the bulk EAN with polar and apolar domains [38]. Addition of salts in the EAN, such as lithium nitrate [39,40], zinc chloride [41] and cerium nitrate [42], shows that they are located in the polar domains and surrounded by nitrate anions.…”
Section: Ethylammonium Nitratementioning
confidence: 99%
“…Several MD calculations have been carried out using parametrized polarizable force fields to account for the polarization induced on the water molecules by the 3+ charge of the Ln cations. , ,, However, it can be quite challenging for polarizable force fields to reproduce the fine balance among the different interactions taking place in the presence of the counterion, especially considering the long simulation time that is required to accurately sample the phase space visited by these systems. On the other hand, in a recent MD simulation study of the whole lanthanide series, a force field without explicit polarization has been developed and it has been found to properly reproduce the structural properties of the Ln 3+ hydration complexes in water and in ethylammonium nitrate . Here, this force field has been used to provide a microscopic description of the Ln 3+ ions in aqueous solutions including counterions having different complexing properties.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in a recent MD simulation study of the whole lanthanide series, a force field without explicit polarization has been developed and it has been found to properly reproduce the structural properties of the Ln 3+ hydration complexes in water 40 and in ethylammonium nitrate. 41 Here, this force field has been used to provide a microscopic description of the Ln 3+ ions in aqueous solutions including counterions having different complexing properties.…”
mentioning
confidence: 99%